KUALITAS FISIK PADA POTONGAN PRIMAL KARKAS SAPI KRUI JANTAN DI KABUPATEN PESISIR BARAT LAMPUNG - Adyan, Haryadi; Septinova, Dian; Sulastri, Sulastri (Jurnal Riset dan Inovasi Peternakan, 2018)
This research aim is to determine the physical quality of primal carcass male Krui cattle in Pesisir Barat District Lampung. This research was conducted on November 2017 in Pesisir Barat District Lampung. The sample used is 5 male Kruicattle.  The research variables are water holding capacity, cooking loss, and pH. Data were analyzed using descriptive analysis. The results of the examination of 5 male Kruicattles with the primal parts of brisket, loin, and round carcasses were average pH values, that is brisket (5.8), loin (5.7), round (5.4); value of  WHC  (Water Holding Capacity), that is  brisket (42,96%), loin (47,14%), and round (45,44%); the average value of cooking loss that is brisket (39,38%), loin (45,46%), and round (43,22%). Key words: male Krui cattle, meat physical quality, Pesisir Barat District